Multiple Shape Coexistence in 110, 112Cd and Beyond Mean Field Calculations. (December 2020) - Garrett, P.E.; Rodríguez, T.R.; Varela, A. Diaz; Green, K.L.; Bangay, J.; Finlay, A.; Austin, R.A.E.; Ball, G.C.; Bandyopadhyay, D.S.; Bildstein, V.; Colosimo, S.; Cross, D.S.; et al.
Abstract: Detailed spectroscopy employing the β + /EC decay of 110, 112 In and the β − decay of 112 Ag has been used to study the excited states of 110, 112 Cd. Low-energy decay branches from highly excited states have been observed and, combined with level lifetimes from the ( n, n ' γ ) reaction, permit B ( E 2) values to be determined thus revealing rotational-like bands built on excited 0 + states and γ bands built on the ground and the shape-coexisting intruder states. The excitation energies of the 0 4 + states appear incompatible with that expected for a pure π(4 p 6 h ) configuration. The experimental results for the 0 + excited states are compared with beyond-mean-field calculations that suggest they possess different shapes, including prolate, oblate, and triaxial.